On the optimal selection of nonsteroidal anti-inflammatory drugs in the management scheme of cataract patients - T.A. Morozova (РМЖ "Клиническая офтальмология")
T.A. Morozova The Cheboksary Branch Of Svyatoslav Fyodorov Eye Microsurgery Federal State Institution Ministry Of Health Of The Russian Federation, Cheboksary, Russian Federation This article aims to review the up-to-date approaches to the control of a non-specific inflammatory response following cataract phacoemulsification with intraocular lens implantation. The authors highlight the key objectives of using nonsteroidal anti-inflammatory agents after cataract surgery during the entire postoperative period, primarily to control inflammatory response and pain and to reduce the risk of cystoid macular edema. The article presents a wide range of data on the outcomes of using various nonsteroidal anti-inflammatory drugs (NSAIDs) in postoperative patients. Over the past years, classical approaches to the selection of patient management schemes have been revised taking into consideration findings of the numerous multicenter trials constructed on the principles of evidence-based medicine. The authors provide rationale for the selection of an optimal anti-inflammatory drug underpinned by the clinical trial results, pharmacodynamic and pharmacokinetic  parameters of NSAIDs of a new generation. The emphasis is made on the use of bromfenac in patients with cataract. In addition, the risk factors and the major strategies of prevention and treatment of macular edema following surgical procedures are reviewed, including those in patients with diabetes mellitus. Keywords: cataract surgery, cystoid macular edema, NSAID, bromfenac, diabetes mellitus, perioperative period. For citation: Morozova T.A. On the optimal selection of nonsteroidal anti-inflammatory drugs in the management scheme of cataract patients. Russian Journal of Clinical Ophthalmology. 2023;23(1):54–59 (in Russ.). DOI: 10.32364/2311-7729-2023-23-1-54-59.